Smuggled into Existence: Nonconsequentialism, Procreation, and Wrongful Disability - Vrousalis, Nicholas (Ethical theory and moral practice, 2013)
The wrongful disability problem arises whenever a disability-causing, and therefore (presumptively) wrongful, procreative act is a necessary condition for the existence of a person whose life is otherwise worth living. It is a problem because it seems to involve no harm, and therefore no wrongful treatment, vis-à-vis that person. This essay defends the nonconsequentialist, rights-based, account of the wrong-making features of wrongful disability. It distinguishes between the person-affecting restriction, roughly the idea that wrongdoing is always the wronging of some person, and the harm principle, the idea that all wrongings are harmings. It argues, first, that the harm principle should be rejected, in light of offending intuitions in salient examples. Rejection of the harm principle is not only independently plausible, but also paves the way for a nonconsequentialist diagnosis of wrongful disability. This diagnosis conceives of wrongdoing as a failure to express adequate respect for the humanity or personhood inherent in the person created. The paper defends a theory of humanity-respecting rights that accommodates plausible intuitions about satisficing and fairness, without resorting to consequentialist premises that lead to well-known impossibility results and paradoxes.